Synthesis and structural characteristics of platinum(II) complexes with N(4)-substituted thiosemicarbazones - Vu, Duong Ba; Dang, Tran Buu (Vietnam Journal of Chemistry, 2016)
Three ligands, namely 4-nitrobenzaldehyde-[N(4)-methyl, N(4)-phenyl thiosemicarbazone] (HL1), fluoren-9-one-[N(4)-(4-methylpiperidinyl)thiosemicarbazone] (HL2), and 4’-hydroxyacetophenone-[N(4)-(4-methylpiperidinyl)thiosemicarbazone] (HL3) as well as three corresponding Pt(II) complexes ([Pt(Li)2](i = 1;2;3)), were synthesized and fully characterized. The analysis of IR, UV-vis, MS, 1H-NMR, 13C-NMR, COSY, and HSQC illustrated that HL1, HL2, HL3 were bidentate ligands and bound to the metal through the imine nitrogen and the net negatively charged sulfur in thiol form. Furthermore, it was demonstrated that the chelating ligands in the Pt(II) complexes were in the trans configuration. Keywords. Thiosemicarbazone, platinum(II) complexes, coordination compounds, inorganic synthesis.